Pengaruh Pelatihan e-Faktur dan QR Code Scanner terhadap Soft Skill Mahasiswa Akuntansi - Zahroh, Fatmawati (Universitas Pendidikan Ganesha, 2021)
Taxation has always undergone a reform called tax reform. Not only the regulations that are undergoing reform but also all sorts of business transactions related to taxes. One of the new ones implemented July 1, 2016 is the reporting of VAT Period SPT with its invoices that use e-invoices. This e-invoice functions to prevent fictitious tax invoices from being ed. The world of work is growing as changes in the system and tax regulations are constantly changing. That's why this research is used in order to improve the soft skills of accounting students in order to compete when graduating and looking for work. The study used experimental methods by conducting e-invoice training and QR code scanners to see the difference between students who were treatment and those who did not. And the results are so significantly different that this has an effect on the soft skills that students who have been treatment training. The results showed that the significance level of 0,000 means there are significant differences that occur in the test of the different effects of training on the soft skills of accounting students. It is expected that there is an ongoing program to hone the soft skills of students in accounting so that they feel soft skills owned by accounting students and able to compete in the world of work.